Avaliação da qualidade de água de captação e saneamento ambiental em Goiás - Souza, Saulo Bruno Silveira e (2014)
It´s known that part of the world illnesses are avoidable and this factor helps improving the management of the water resources ,drinking water supplying, sanitation and hygiene. The global importance of these interventions was recognized in the Milleniun Development Objective (MDO), and it means half reduction of the proportion of people that do not have access to drinking water and basic sanitation concerning the period from 1990 to 2015. This way, knowing and identifying the hydrographic bays panorama in the state of Goiás is essential so for the development of strategies and implementation of programs in order to have improvements on the infra-structure and consequently in sanitation and health. To achieve this aim, indexes that bring information about the hydrographic bays situation were built up and they are related to two aspects: water quality and environmental health focusing sanitation. The indexes construction process envolved a series of decisions as well as an integrated environmental conception and consequently an interdisciplinarian approach that considered the environmental, demographic, behavioural, cultural and socioeconomical issues. Relaying the Water Quality Index (WQIpca)elaboration, multifactorial statistics and the methods of least ordinary squares, were used and the index was applied in 180 sample points in the Goias state waters which were monthly evaluated in the period from 2005 to 2009. Observering the analysis, it´s possible to point out that there is a strong relation among the areas that have the higher index of remanescent and the municipalities that have higher water quality index (WQIpca); it means better water quality. It´s also added that in relation to all of the years analysed, there is improvement in the water quality in the period of droughts. The revealed index was characterized as robust and it can also be applied for some other Brazilian rivers. Considering the construction of the environmental health index, focusing sanitation, the FPSEEA model (motriz force, pressure, state, exposition, effect and action) was applied and the same model structured the IGLOBAL index and it was the basis for the variables choice (totalizing 27 indicators) that represent the environmental, sanitation and public health changes. Relaying the definition of weights that would compose the index, the principal component analysis (PCA) was used. In terms of the verification of the robustness index and indicators´ sensibility, fours indexes were calculated, and equal weights and indicators rates as well as calculated weights, using multivariable statistics were applied. It´s also mentioned that for each of these situations, two padronizations were used: on the first one, the values represent zero as average and padronized deviation as being one; on the second padronization, the indicators have maximum value as one and minimum value as zero. So for checking the sensibility of the indicators, some indexes were calculated, considering the possibility of information absence. It means the elimination of one indicator. Finally, it was observed that the proposed index is robust, it has a good response and it also makes a large and integrated vision of the health, environmental hydrographic bays conditions.